Ferroelectric characteristics of SrBi2Ta2O9 thin films fabricated by the radio frequency magnetron sputtering deposition technique - Lee, JK; Song, TK; Jung, HJ (ELSEVIER SCIENCE SA, 1998)
SrBi(2)Ta(2)O(9)thin films were successfully fabricated by the radio frequency magnetron sputtering deposition method. The crystal structure of SrBi2Ta2O9 thin films grown on the Pt(111) layer was preferentially c-axis oriented. Surface microstructure shows the mixture of two kinds of morphologies. The Pt/SBTO/Pt capacitor shows P-r(*) - P-r(boolean AND) = 16.3 mu C/cm(2) and E-c = 50 kV/cm. After a fatigue test, the polarization versus electric field loop shifted toward a positive electric field. The interface between platinum and titanium layer was changed by the inter-diffusion of the Pt, Ti, O atoms after post-annealing at 800 degrees C for 2 h. (C) 1998 Elsevier Science S.A.
Keywords: CAPACITORS; FATIGUE; PB(ZR,TI)O-3; ELECTRODES; BEHAVIOR